In vitro antimicrobial activity of plant extracts against Pseudomonas syringae pv. actinidiae causal agent of bacterial canker in kiwifruit. (2nd January 2020) - Simonetti, Giovanna; Pucci, Nicoletta; Brasili, Elisa; Valletta, Alessio; Sammarco, Iris; Carnevale, Eleonora; Pasqua, Gabriella; Loreti, Stefania
Abstract: Pseudomonas syringae pv. actinidiae (Psa), the causal agent of bacterial canker of kiwifruit, is considered the main pathogen of yellow-, green- and red-fleshed kiwifruit. All major kiwifruit producing countries in the world have been affected by this bacterial pathogen, leading to substantial economic losses. The control of bacterial canker of kiwifruit is based only on preventive methods or on the use of copper compounds that can cause phytotoxicity problems. In this study, the in vitro antibacterial activity of seven different plant extracts against eight Psa strains has been evaluated. The inhibition of 100% of the Psa growth was observed, after 24 h, for the extracts of Polygonum cuspidatum roots (POL-roots), Hypericum perforatum roots elicited with chitosan oligosaccharides (HYP-COS roots) and non-fermented grape pomace (ITA-pomace). The strongest antibacterial activity was exhibited by POL-roots, with a geometric mean of minimum inhibitory concentration of 100% of growth (GMMIC100 ) of 105.11 µg/mL after 24 h, and with a GMMIC100 value of 148.65 µg/mL after 48 h. Moreover, POL-roots extract showed the best bactericidal activity with a GMMBC of 210.22 µg/mL. No phytotoxic activity was observed up to 15 days in the leaves of Actinidia chinensis "Belen" treated with plant extracts at 500 µg/mL.